Blockchain-Integrated System Architecture for Secure and Transparent Data Transactions - Wajihi Ali; Md. Kamal Khan; Walid Nguia; Okouma Nguia (The Eastasouth Journal of Information System and Computer Science, 2023)
The growing demand for secure, transparent, and efficient data transaction systems has highlighted the limitations of traditional centralized architectures, particularly in terms of data integrity, trust, and vulnerability to cyber threats. This study proposes a blockchain-integrated system architecture designed to enhance the security and transparency of data transactions. The proposed framework combines layered system design with decentralized blockchain technology, incorporating user, application, blockchain, off-chain storage, and security layers to ensure robust data handling and verification. The architecture leverages cryptographic techniques such as hashing, encryption, and digital signatures to ensure data confidentiality, integrity, and authentication. Additionally, the use of off-chain storage mechanisms addresses scalability challenges by storing large datasets externally while maintaining verifiable references on the blockchain. The workflow emphasizes the role of distributed consensus mechanisms in ensuring transaction legitimacy and preventing unauthorized modifications. By recording transaction hashes on an immutable ledger, the system enables transparent and tamper-proof data verification. The integration of blockchain with traditional architecture offers significant advantages, including decentralization, enhanced security, and improved auditability. However, challenges such as scalability, latency, and interoperability remain areas for further research. Overall, the proposed blockchain-integrated system provides a comprehensive framework for secure and transparent data transactions, making it suitable for applications across various domains, including finance, healthcare, and supply chain management.